ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI LABA UMKM GERABAH DI KABUPATEN KLATEN - Astuti, Linda; Triyanto, Eko (Jurnal Riset Rumpun Ilmu Ekonomi, 2023)
This study aims to determine the effect of Capital, Quality Costs, Selling Prices, and Digital Marketing on the Profit of Pottery MSMEs in Klaten Regency. This type of research uses quantitative research. The population of pottery MSMEs in Klaten Regency is 400 MSMEs with a total research sample of 80 respondents confirmed using the Slovin formula. The results showed that partially the Capital variable had a significant effect on the profit of pottery MSMEs in Klaten Regency. The Selling Price has a significant effect on the Profit of pottery MSMEs in Klaten Regency while the Quality Cost does not have a significant effect on the Profit of Pottery MSMEs in Klaten Regency and Digital Marketing does not have a significant effect on the Profit of Pottery MSMEs in Klaten Regency.